2021
DOI: 10.3390/ma14247565
|View full text |Cite
|
Sign up to set email alerts
|

Pin Angle Thermal Effects on Friction Stir Welding of AA5058 Aluminum Alloy: CFD Simulation and Experimental Validation

Abstract: The friction stir welding (FSW) of tool pin geometry plays a critical role in the final properties of the produced joint. The tool pin geometry directly affects the generation of heat and the flow of internal materials during the FSW process. The effects of the FSW tool pin angle on heat generation and internal flow have not been quantitatively investigated in detail. In this manuscript, a validated Computational Fluid Dynamic (CFD) model was implemented to analyze the effects of pin angle on the thermo-mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…FSSW tools made from tungsten carbide (WC) with a cylindrical probe (length: 0.9 mm, diameter: 8.2 mm) and shoulder diameter of 20 mm were used. There are many design considerations for manufacturing of FSW and FSSW tools [43][44][45]. However, the tool material was selected based on the tool material required for welding high-melting-point materials, as the work deals with both steel and copper alloys.…”
Section: Friction Stir Spot Welding (Fssw)mentioning
confidence: 99%
“…FSSW tools made from tungsten carbide (WC) with a cylindrical probe (length: 0.9 mm, diameter: 8.2 mm) and shoulder diameter of 20 mm were used. There are many design considerations for manufacturing of FSW and FSSW tools [43][44][45]. However, the tool material was selected based on the tool material required for welding high-melting-point materials, as the work deals with both steel and copper alloys.…”
Section: Friction Stir Spot Welding (Fssw)mentioning
confidence: 99%
“…Achieving the capacity of the above theory is a goal of researchers that requires easy passage of oxygen and proper conduction of electrons and ions with no blockage of cavities [192][193][194][195]. It has been found that a suitable geometric structure with two pore dimensions, one with large dimensions for the passage of oxygen gas and the other with small mesoporous cavities, provides a suitable result for the reaction and placement of lithium oxide [191,196,197].…”
Section: Graphene Is Engineered In Cathode Fabricationmentioning
confidence: 99%
“…where, A r is any small area on the tool-BM interfaces, r is the radial distance of the center of the area from the tool axis, V is the control-volume enclosing the area A r , τ is the BM shear stress and θ is the angle with the negative x-axis in the counter-clockwise direction, η is defined as the mechanical efficiency, δ denotes the spatially variable fractional slip between the tool and the BM interface, µ f is the friction coefficient, ω is the rotational velocity, and P N is the axial pressure. The generated heat by plastic deformation (Q p ), can be calculated as [60]:…”
Section: Boundary Conditionsmentioning
confidence: 99%